Biological denitrification potential of cellulase-producing Cupriavidus sp. ZY7 and denitrifying Aquabacterium sp. XL4 at low carbon-to-nitrogen ratio: Performance and synergistic properties. (September 2022) - Zhai, Zhenyu; Su, Junfeng; Ali, Amjad; Xu, Liang; Wahid, Fazli
Graphical abstract: Highlights: Strain ZY7 exhibits excellent synergistic effect with strain XL4 at low C/N ratio. Cellulose is degraded to readily utilizable carbon source for denitrification strain. Hydrolysis of β-1, 4-glycosidic bonds and oligosaccharides as rate-limiting steps. Aromatic protein will be catabolized and consumed in the co-culture environment. Abstract: This study emphasizes on the cellulase production characteristics of strain ZY7 and its collaboration with nitrate-dependent ferrous oxidizing (NFO) strain XL4 to achieve efficient denitrification at low carbon-to-nitrogen (C/N) ratio. Results indicated that the denitrification efficiency increased from 65.47 to 97.99% at 24 h after co-culture at C/N of 1.0. Three-dimensional fluorescence excitation-emission matrix (3D-EEM) showed significant changes in the intensity of soluble microbial products (SMP), fulvic-like materials, and aromatic proteins after co-culture. Bio-precipitates were characterized by Scanning electron microscope (SEM), Fourier transform infrared spectrometer (FTIR), and X–ray diffraction (XRD), which showed that cellulose structure was disrupted and the metabolites were potential carbon source for denitrification. In addition, cellulase activity suggested that the hydrolysis of β-1, 4-glycosidic bonds and oligosaccharides may be the rate-limiting steps in cellulose degradation. This work promoted the understanding of denitrification characteristics of co-culture and expanded the application of cellulose degrading bacteria in sewage treatment.